2015
DOI: 10.1007/s12013-014-0501-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic miR-145 Mimic Enhances the Cytotoxic Effect of the Antiangiogenic Drug Sunitinib in Glioblastoma

Abstract: Although aggressive therapeutic regimen has been applied in the treatment of Glioblastoma (GBM), the prognosis of patients with GBM remains poor. Preclinical studies have demonstrated the efficacy of Suntinib in GBM both in vitro and in vivo. In this study, we showed that the cytotoxicity was enhanced by transfection with miR-145 mimic. In addition, we suggested that the enhanced cytotoxicity of Sunitinib by miR-145 mimic was mediated by inhibition of both P-gp and Bcrp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…[39][40][41][42][43] Correlation analyses between genome-wide miRNA expression and BCRP/ABCG2 protein expression in ccRCC patients of Cohort 2 did not reveal any significant association. [39][40][41][42][43] Correlation analyses between genome-wide miRNA expression and BCRP/ABCG2 protein expression in ccRCC patients of Cohort 2 did not reveal any significant association.…”
Section: Discussionmentioning
confidence: 85%
“…[39][40][41][42][43] Correlation analyses between genome-wide miRNA expression and BCRP/ABCG2 protein expression in ccRCC patients of Cohort 2 did not reveal any significant association. [39][40][41][42][43] Correlation analyses between genome-wide miRNA expression and BCRP/ABCG2 protein expression in ccRCC patients of Cohort 2 did not reveal any significant association.…”
Section: Discussionmentioning
confidence: 85%
“…A similar example of the power of combining miRNA-based therapy with anti-angiogenic agents was shown in a study by Liu et al Here, miR-145 mimics were combined with sunitinib on U87 cells which showed additive effects, even though very high concentrations of sunitinib were used [74]. It must be noted, however, that both studies only addressed tumor cell biology and not inasmuch tumor angiogenesis.…”
Section: Anti-angiogenic Mirna-based Combination Therapymentioning
confidence: 83%
“…Since miR‐145 has been identified as an inhibitor of BCRP and P‐gp (Liu et al, b), the effect of TGF‐β1 on miR‐145 expression were examined in HepG2 cells. The results showed that TGF‐β1 markedly downregulated miR‐145 expression in HepG2 cells (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that TGF‐β1 upregulated HOTAIR expression through SMAD4, and the upregulation of HOTAIR reduced miR‐145 expression through the HOTAIR/PRC2 pathway. miR‐145 inhibited P‐gp and BCRP expression (Liu et al, a), while miR‐145 inhibitor upregulated the expression of P‐gp and BCRP. P‐gp and/or BCRP overexpression enhanced drug efflux transport in hepatocellular carcinoma cells, resulting in a decrease of intracellular drug concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation